Transformasional Leadership Sebagai Kunci Sukses Pengelolaan Koperasi Sekolah - Tarisa Kinasih; Fatma Aqila; Ikke Nur Khasanah; Zahwa Haifa Aqilah; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
School School cooperatives play a role in fostering entrepreneurial skills and student independence, but they still face obstacles such as lack of innovation, low participation, and weak leadership. This study aims to examine the role of transformational leadership in improving the management of school cooperatives through a literature review. The results indicate that transformational leadership can improve cooperative performance by encouraging member motivation, active participation, and innovation. Therefore, its implementation is key to achieving effective, innovative, and sustainable cooperative management.